2012
DOI: 10.1111/j.1365-2427.2012.02804.x
|View full text |Cite
|
Sign up to set email alerts
|

Grazing management influences the subsidy of terrestrial prey to trout in central Rocky Mountain streams (USA)

Abstract: Summary 1. Research in forest and grassland ecosystems indicates that terrestrial invertebrates that fall into streams can be an important prey resource for fish, providing about 50% of their annual energy and having strong effects on growth and abundance. However, the indirect effects of land uses like cattle grazing on this important prey subsidy for stream salmonids are unclear. 2. During summer 2007, we compared the effects of three commonly used grazing systems on terrestrial invertebrate inputs to stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 71 publications
3
51
0
Order By: Relevance
“…Age‐0 fish [< 50 mm fork length (FL) for Brook Trout Salvelinus fontinalis and < 60 mm FL for Brown Trout Salmo trutta ] are not sampled effectively using this method and were excluded from all analyses (Saunders, Fausch & White ). Estimates of capture probability and abundance for fish larger than age 0 were calculated in Program MARK (White & Burnham ; Saunders, Fausch & White ) using the Huggins closed‐population estimator, incorporating species identity and FL as individual covariates and pooling data across the nine sites with two‐pass data to improve capture estimates (Saunders & Fausch ).…”
Section: Methodsmentioning
confidence: 99%
“…Age‐0 fish [< 50 mm fork length (FL) for Brook Trout Salvelinus fontinalis and < 60 mm FL for Brown Trout Salmo trutta ] are not sampled effectively using this method and were excluded from all analyses (Saunders, Fausch & White ). Estimates of capture probability and abundance for fish larger than age 0 were calculated in Program MARK (White & Burnham ; Saunders, Fausch & White ) using the Huggins closed‐population estimator, incorporating species identity and FL as individual covariates and pooling data across the nine sites with two‐pass data to improve capture estimates (Saunders & Fausch ).…”
Section: Methodsmentioning
confidence: 99%
“…We expected this effect to be particularly strong for low elevation sites where there is greater riparian disturbance from cattle grazing (Li et al. , Saunders and Fausch , ). We calculated NDVI based on surface reflectance Landsat images (Landsat 5, 7, and 8) using Google Earth Engine (Gorelick et al.…”
Section: Case Study: Lahontan Cutthroat Troutmentioning
confidence: 99%
“…Fortunately, researchers have started to value the importance of crosssystem subsidies while restoring or managing aquatic and terrestrial ecosystems [12,170]. Saunders and Fausch (2012) compared the impacts of three general grazing systems on terrestrial invertebrate subsidies to adjacent streams and their consumption by trout in northern Colorado [171]. They found that rotational grazing management (either intensive or simple) led to more riparian vegetation, higher input of terrestrial invertebrates, greater terrestrial invertebrate consumption by trout.…”
Section: Implications Of Resource Subsidies For Ecosystem Conservationmentioning
confidence: 99%
“…They found that rotational grazing management (either intensive or simple) led to more riparian vegetation, higher input of terrestrial invertebrates, greater terrestrial invertebrate consumption by trout. Rotational grazing systems can effectively maintain terrestrial invertebrate subsidies, which were needed to sustain robust trout populations [171].…”
Section: Implications Of Resource Subsidies For Ecosystem Conservationmentioning
confidence: 99%